2022
DOI: 10.3390/antibiotics11121755
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus from Diabetic Foot Infections in a Tunisian Hospital with the First Detection of MSSA CC398-t571

Abstract: This study sought to analyze the antimicrobial resistant phenotypes and genotypes as well as the virulence content of S. aureus isolates recovered from patients with diabetic foot infections (DFIs) in a Tunisian hospital. Eighty-three clinical samples of 64 patients were analyzed, and bacterial isolates were identified by MALDI-TOF. The antimicrobial resistance phenotypes were determined by the Kirby–Bauer disk diffusion susceptibility test. Resistance and virulence genes, agr profile, spa and SCCmec types wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…While the distribution of gram-negative bacteria varies across the continent, Staphylococcus aureus remains the dominant gram-positive isolate as is the case across the globe, emphasizing its role in skin and soft tissue infections. 22–24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the distribution of gram-negative bacteria varies across the continent, Staphylococcus aureus remains the dominant gram-positive isolate as is the case across the globe, emphasizing its role in skin and soft tissue infections. 22–24 …”
Section: Discussionmentioning
confidence: 99%
“…While the distribution of gramnegative bacteria varies across the continent, Staphylococcus aureus remains the dominant gram-positive isolate as is the case across the globe, emphasizing its role in skin and soft tissue infections. [22][23][24] Another likely explanation for the observed variation in bacterial species isolated across countries and regions of Africa could be the sample specimen used for microbiological assessment which is wound swabs in the case of Uganda. In practice, wound care providers have often adopted wound biopsies (tissue), swabs, curettage, and wound aspirate as principal samples.…”
Section: Discussionmentioning
confidence: 99%
“…The putative advantages of certain S. aureus clones for surviving and persisting in the very particular niche of the DFU have been evaluated by several groups. In all the studies, the S. aureus population colonizing or infecting the DFU was highly diverse, as determined by molecular typing methods [67,71,72,107,108]. However, certain clones were predominant in some geographical regions.…”
Section: Major Clones Of S Aureus That Colonize and Infect Skin Ulcer...mentioning
confidence: 99%
“…A recent study conducted with patients from a Tunisian hospital, comprising individuals from different areas in Africa, showed the presence of linages CC5, CC8, CC1, and CC15 among MRSA and lineages CC1, CC12, CC22, and CC398 among MSSA. The strains belonging to CC1 were all spa type t127, a genotype associated with severe infections in the United States and Germany [107]. The molecular characterization of S. aureus isolates from patients with DFU monomicrobial infection in France showed that 18 CCs and 11 ST were found, but 38% of the isolates from patients with diabetic foot osteomyelitis (DFOM) belonged to the MSSA CC398 lineage, whereas 16% of the isolates from patients presenting only skin and soft tissue infection (SSTI) were CC45.…”
Section: Major Clones Of S Aureus That Colonize and Infect Skin Ulcer...mentioning
confidence: 99%
See 1 more Smart Citation